Analisis Penyalahgunaan Kawasan Tepi Jalan menjadi Tempat Pembuangan Sampah Liar di Jalan Sipirok Area, Kec. Percut Sei Tuan, Kab. Deli Serdang - Rayhan Fadilah; Lisna Anggia Fortunata; Della Fazera; Iin Arsenna Br. Sembiring; Alvin Pratama (Yayasan Literasi Sains Indonesia, 2024)
Waste causes serious problems if not managed properly. Garbage problems generally occur due to the behavior of people who like to throw rubbish carelessly. Littering has the potential to create illegal rubbish dumps in public places, including the sides of roads. In Deli Serdang Regency, there are several public roads which are often misused as illegal rubbish dumps, one of which is Jalan Sipirok Area which is in Kenangan Village, Kec. Percut Sei Tuan. This research aims to identify cases of misuse of roadside areas as illegal rubbish dumps on Jalan Sipirok, Kenangan Village, Percut Sei Tuan District. The research method used was a qualitative descriptive method through observation, interviews and literature review with various relevant references. Based on the research results, it was found that the roadside area at the location was abandoned land that was not utilized so that people were free to throw away rubbish. Community participation is still low in the waste problem coupled with the lack of support from the government in eradicating cases of careless waste disposal. Disposal of this waste has many negative impacts, such as unpleasant odors, damaging the beauty of the environment, and increasing the risk of accidents.